2019
DOI: 10.3390/ijms20030502
|View full text |Cite
|
Sign up to set email alerts
|

Post-Injury Neuroprotective Effects of the Thalidomide Analog 3,6′-Dithiothalidomide on Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major cause of mortality and disability worldwide. Long-term deficits after TBI arise not only from the direct effects of the injury but also from ongoing processes such as neuronal excitotoxicity, inflammation, oxidative stress and apoptosis. Tumor necrosis factor-α (TNF-α) is known to contribute to these processes. We have previously shown that 3,6′-dithiothalidomide (3,6′-DT), a thalidomide analog that is more potent than thalidomide with similar brain penetration, selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Unlike larger molecules, it is readily capable of crossing the BBB (Tweedie et al, 2007;Boi et al, 2019). Therefore, Thalidomide and its analogs are promising candidate agents for evaluation in a variety of neurological disorders underpinned by neuroinflammation (Tweedie et al, 2007(Tweedie et al, , 2012Yoon et al, 2013;Wang et al, 2016;Batsaikhan et al, 2019;Tsai et al, 2019). In PD models, Thalidomide and the analog Lenalidomide, administered at the same dose of 100 mg/kg p.o.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike larger molecules, it is readily capable of crossing the BBB (Tweedie et al, 2007;Boi et al, 2019). Therefore, Thalidomide and its analogs are promising candidate agents for evaluation in a variety of neurological disorders underpinned by neuroinflammation (Tweedie et al, 2007(Tweedie et al, , 2012Yoon et al, 2013;Wang et al, 2016;Batsaikhan et al, 2019;Tsai et al, 2019). In PD models, Thalidomide and the analog Lenalidomide, administered at the same dose of 100 mg/kg p.o.…”
Section: Discussionmentioning
confidence: 99%
“…However, rutin suppressed the increase of TNF-α and NF-ĸB in TBI. TNF-α, and NF-ĸB have been documented to be cytokines responsible for the inflammatory process of secondary TBI injury (24,25). Gugliandolo et al have shown that TNF-α and NF-ĸB production increased following TBI, and also injury regressed in brain tissue where TNF-α and NF-ĸB production was suppressed (26).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the contusion volume in the ipsilateral cortex 72 h after TBI, cresyl violet-stained sections were digitized and analyzed by using ImageJ (National Institutes of Health, Bethesda, MD, USA) as previously reported [31]. The volume was computed by adding the injury areas and multiplying with the inter-slice distance (500 µm).…”
Section: Contusion Volume Assessmentmentioning
confidence: 99%